2014
DOI: 10.1093/sysbio/syu018
|View full text |Cite
|
Sign up to set email alerts
|

Species Delimitation using Genome-Wide SNP Data

Abstract: The multispecies coalescent has provided important progress for evolutionary inferences, including increasing the statistical rigor and objectivity of comparisons among competing species delimitation models. However, Bayesian species delimitation methods typically require brute force integration over gene trees via Markov chain Monte Carlo (MCMC), which introduces a large computation burden and precludes their application to genomic-scale data. Here we combine a recently introduced dynamic programming algorith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
336
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(339 citation statements)
references
References 37 publications
(60 reference statements)
3
336
0
Order By: Relevance
“…In addition to the SNAPP runs described above, we performed a species delimitation analysis as implemented in BFD* (Leaché et al, 2014) to further test for phylogenetic differentiation among genetic clusters. Because BFD* relies on SNAPP, this analysis was subject to similar computational demands as those described above.…”
Section: Species Tree Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the SNAPP runs described above, we performed a species delimitation analysis as implemented in BFD* (Leaché et al, 2014) to further test for phylogenetic differentiation among genetic clusters. Because BFD* relies on SNAPP, this analysis was subject to similar computational demands as those described above.…”
Section: Species Tree Analysesmentioning
confidence: 99%
“…Highthroughput sequencing technologies, novel cost-effective methods for constructing reduced representation libraries (that is, restriction siteassociated DNA sequencing (RADseq); and the development of statistical approaches that allow historical demographic analyses of these data (that is, Gutenkunst et al, 2009;Excoffier et al, 2013;Leaché et al, 2014) are important factors contributing to this transformation. These novel genomic-scale data sets can reveal cryptic genetic diversity within recognized taxa, estimate demographic parameters characterizing populations and identify important recent and historical events that have shaped existing genetic diversity, such as hybridization between lineages (Luikart et al, 2003;Ellegren, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Sanaga River is, for example, a biogeographic barrier to gene flow between Chimpanzee populations distributed on either side of it, although occasional hybridization occurs (Gonder et al 2011). A phylogeographic study based on genome-wide single nucleotide polymorphims of Hemidactylus geckos also suggested a role for the Sanaga River acting as a barrier to gene flow (Leaché et al 2014). Other studies revealed no impact of the Sanaga River on the broad scale phylogeographic structure of terrestrial vertebrates, with individuals sampled on both side of the river being part of the same terminal clade (Nicolas et al 2008(Nicolas et al , 2010.…”
Section: The Dahomey Gap and Lower Niger River Acted As Biogeographicmentioning
confidence: 99%
“…Nesi et al 2013, Leaché et al 2014. For example, no haplotypes were shared between morphologically similar populations sampled across the Dahomey gap for two songbird species, Stiphrornis erythrothorax (Beresford and Cracraft 1999;Schmidt et al 2008) and Hylia prasina (Marks 2010).…”
mentioning
confidence: 99%
“…In addition, there are a number of approaches to species delimitation that incorporate model selection. These include methods that identify the optimal species delimitation using likelihood ratio tests (70), reversible-jump Markov chain Monte Carlo (71,72), information theory (73), ABC (74), and marginalized likelihoods (75). Methods for analyzing comparative phylogeographic data are also under active development, including the use of hierarchical Bayesian models to test simultaneous divergence (76,77) or simultaneous population expansion (78,79).…”
Section: Resultsmentioning
confidence: 99%